Prevalence, awareness, treatment, and control of hypertension in older people: results from the population-based KORA-age 1 study - Muli, Samuel; Meisinger, Christa; Heier, Margit; Thorand, Barbara; Peters, Annette; Amann, Ute (BMC public health, 2020)
Background Hypertension remains a significant modifiable risk factor for cardiovascular diseases and a major determinant of morbidity and mortality. We aimed to describe sex-stratified age-standardized estimates of prevalence, awareness, treatment and control of hypertension, and their associated factors in older adults. Methods The KORA-Age1 is a population-based cross-sectional survey carried out in 2008/2009 on individuals aged 65–94 years in Augsburg region, Germany. Blood pressure measurements were available for 1052 out of 1079 persons who participated in the physical examination. Factors associated with prevalence, awareness and control of hypertension were investigated by multivariable logistic regression. Results The overall prevalence of hypertension (≥140/90 mmHg) was 73.8% [95% confidence interval (CI), 69.3–77.9], representing 74.8% (95% CI, 68.4–80.2) in men and 73.5% (95% CI, 66.8–79.3) in women. Among those with hypertension, 80.2% (95% CI, 75.3–84.4) were aware of their hypertensive condition and 74.4% (95% CI, 69.2–79.1) were on treatment for hypertension. Among those aware of their hypertension status, 92.8% (95% CI, 88.8–95.6) were on treatment and 53.7% (95% CI, 47.0–60.1) had their blood pressure controlled. Hypertension was more frequent in individuals who were older, obese, or had diabetes. Higher education attainment or presence of comorbidities was associated with higher level of hypertension awareness. Individuals taking three antihypertensive drug classes were more likely to have controlled hypertension compared with those taking one antihypertensive drug class, odds ratio (OR), 1.85 (95% CI, 1.14–2.99). Conclusion Our findings identified high prevalence of hypertension and relevant health gaps on awareness, treatment and suboptimal control of hypertension in older adults in Germany. Screening for hypertension should especially target older adults with low educational attainment and ‘healthy’ elderly with less contact to physicians.